2005
DOI: 10.3748/wjg.v11.i42.6662
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective activity ofNigella sativaL oil and its constituent, thymoquinone against acute alcohol-induced gastric mucosal injury in rats

Abstract: Both NS and TQ, particularly NS can partly protect gastric mucosa from acute alcohol-induced mucosal injury, and these gastroprotective effects might be induced, at least partly by their radical scavenging activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(106 citation statements)
references
References 28 publications
12
92
0
2
Order By: Relevance
“…In fact, N. sativa attenuates the damage to β-cells of the pancreas following exposure to toxic elements such as cadmium [9] . Similarly, N. sativa administration attenuates the ulcerative effects of ethanol on gastric mucosa by decreasing the glutathione-S transferase levels in gastric mucosa [10] . Besides these effects, N. sativa also demonstrates antiparasitic effects.…”
Section: To the Editormentioning
confidence: 99%
“…In fact, N. sativa attenuates the damage to β-cells of the pancreas following exposure to toxic elements such as cadmium [9] . Similarly, N. sativa administration attenuates the ulcerative effects of ethanol on gastric mucosa by decreasing the glutathione-S transferase levels in gastric mucosa [10] . Besides these effects, N. sativa also demonstrates antiparasitic effects.…”
Section: To the Editormentioning
confidence: 99%
“…A previous study reported that TQ could protect gastric mucosa from acute alcohol-induced mucosal injury, and that this gastroprotective effect might be induced by its radical-scavenging activity. [26] In addition, hepatoprotective effects of TQ against several hepatotoxic agents have been reported, which were attributed to its antioxidant activity. [27][28][29] It was also reported that TQ could be used to treat ethanol-induced hepatotoxicity because of its antioxidant and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental evidences proved that the herbs have gastro protective activities against gastric mucosal injury induced by ethanol 21 , ischemia reperfusion 22 , indomethacin 21 , alcohol toxicity 23 or stress 24 in rat. Herb-induced gastro protection mechanism varies according to the nature and chemical constituents of the herbs.…”
Section: Herbal Treatment For Peptic Ulcermentioning
confidence: 99%